Energy recovery from tubular microbial electrolysis cell with stainless steel mesh as cathode - Ma, Xiaoli (R Soc Open Sci, 2017)
In comparison to the transportation and storage of hydrogen, methane has advantages in the practical application, while the emerging product termed as ‘biohythane’ could be an alternative to pure hydrogen or methane in a new form of energy recovery from microbial electrolysis cell (MEC). However, the cathodic catalyst even for biohythane still bothers the performance and cost of total MEC. Herein, we fabricated the MEC reactor with surrounding stainless steel mesh (SSM) to investigate the feasibility of stainless steel mesh as an alternative to precious metal in biohythane production. The columbic efficiency (CE) of anode was around at 80%, representing the SSM would not limit the activity of anodic biofilm; the SEM image and ATP results accordingly indicated the anodic biofilm was mature and well constructed. The main contribution of methanogens that quantified by qPCR belonged to the hydrogenotrophic group (Methanobacteriales) at cathode. The energy efficiency reached more than 100%, reached up to approximately 150%, potentially suggesting the energetic feasibility of the application to obtain biohythane with SSM in scale-up MEC. Benefiting from the likely tubular configuration, the ohmic resistance of cathode was very low, while the main limitation associated with charge transfer was mainly caused by biofilm formation. The total performances of SSM used in the tubular configuration for biohythane production provide an insight into the implementation of non-precious metal in future scale-up pilot with energy recovery.